Recorrências temáticas na poética de Inês Pedrosa: erotismo, amizade, memória e morte - Rocha Filho, Ulysses (2013)
We have developed, in this work, a study of poetic lines of novels in the portuguese novelist Inês Pedrosa (1962). Recurrent approaches will be investigated, such as: the friendship, the memory, the eroticism and the death in their main novels: A Instrução dos Amantes (1992), Nas tuas Mãos (1997), Fazes-me Falta (2002), A Eternidade e o Desejo (2007) e Os Íntimos (2010). For both, we will depart for a systematic reflexive about friendship, time and memory to understand the ramifications originated from reports of multiple and diverse characters that are on the border of life/death. The hybrid narratives (TADIÉ, 1978) become, in this way, multiple or mirrored. Based on the premise of the constitution of the identity of the female (BATAILLE, 1980; PAZ, 2001), will be prioritized the elements of poetic tissues which divides the reminiscence and allow the presentation of works from the perspective of cultural studies of contemporaneity (BAUMAN, 2003, 2005-b, 2005-d; CEVASCO, 2003).